PSYCHOLOGICAL APPROACHES IN SUPPORT OF PSYCHOTHERAPY (Universal International Scientific Journal, 2026)
The articles were written to gain broad knowledge in the field of psychotherapy and to be used for scientific work. The article covers a wide range of psychotherapy approaches and procedures.
Keywords: Psychological prevention, phenomenological approach, cognitive behavioral therapy, emotional disorders.